2018
DOI: 10.1186/s13063-018-2548-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of electroacupuncture for post stroke depression: study protocol for a randomized controlled trial

Abstract: BackgroundPoststroke depression is closely related to increased mortality in stroke patients. Compared with antidepressants, electroacupuncture (EA) treatment for poststroke depression (PSD) has relatively more stable effectiveness and can reduce side effects. This trial is designed to provide solid evidence for the efficacy and safety of EA treatment for patients with PSD.Methods/designThis ongoing study is a single-blind, single-center, parallel group, randomized controlled trial. Sixty-two participants will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…It was considered that an increase of 8.5 points in the EA group relative to the sham EA group would represent a clinically meaningful difference. 23 Considering a 5% false positive error (α = 0.05, two-sided) and 80% power (β = 0.2), the sample size was calculated as (5) verified in the pilot study), a total sample size of at least 64 participants was needed for the trial.…”
Section: Sample Sizementioning
confidence: 99%
“…It was considered that an increase of 8.5 points in the EA group relative to the sham EA group would represent a clinically meaningful difference. 23 Considering a 5% false positive error (α = 0.05, two-sided) and 80% power (β = 0.2), the sample size was calculated as (5) verified in the pilot study), a total sample size of at least 64 participants was needed for the trial.…”
Section: Sample Sizementioning
confidence: 99%
“…Poststroke depression (PSD) is characterized by anxiety, disordered sleep, hopelessness, and lowered responsiveness and is a common stroke complication [ 46 ]. Cai et al show that EA stimulation might be safe and effective for treating poststroke depression (PSD) in clinic [ 8 ]. Acupuncture plus auricular point sticking are effective and safe for poststroke depression (PSD).…”
Section: The Therapeutic Effect Of Ea For Ischemic Stroke In Clinimentioning
confidence: 99%
“…As a relatively feasible, simple, and cheap therapy, it is commonly accepted by stroke patients in clinic [ 7 ]. The clinical effectiveness of EA in stroke rehabilitation has been demonstrated in numerous studies [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the treatment of PSD, antidepressants such as citalopram, escitalopram, nortriptyline, milnacipran, mirtazapine, piracetam, and fluoxetine are most commonly used. [ 12 ] However, adverse effects of antidepressants were evident, including blurred vision, urinary retention, low blood pressure, sexual dysfunction, tremors, and severe insomnia. [ 13 ] And 1 study showed that up to 60% of patients do not respond adequately to antidepressant treatment.…”
Section: Introductionmentioning
confidence: 99%